ANALISIS TEKNIK PENERJEMAHAN KALIMAT IMPERATIF PADA FILM MULAN 2020: - - Nur Hasyim; Unique Aprilia Putri Tami (Epigram, 2025)
The purpose of this study is to identify the technique of imperative sentences in the film Mulan 2020. This study used content analysis and questionnaires.This research used a descriptive qualitative, and focuses on research questions: the translation techniques found in the film and the translation techniques most widely used by translators in translating imperative sentences in the film Mulan 2020. The results of this study found 13 types of translation techniques from 420 data, namely the common equivalent of 317 data or 75.48%; the modulation is 42 data or 10%;